EXPLANATION OF THE EFFECT OF LOANS ON THE PERFORMANCE OF COMMERCIAL BANKS WITH RATE ANALYSIS - GERMİR, Hatice Nur (EUROASIA JOURNAL OF SOCIAL SCIENCES & HUMANITIES, 2019)
The performances of the banks, which constitute the largest segment of the financial system, are of great importance for the national economy. Savings deposits they have collected from their owners, entrepreneurs and institutions from the beginning of the load on the shoulders of the banks that transfer funds to those who request one more floor is underdeveloped due to other financial institutions in Turkey. The sharp fluctuations in foreign exchange and exchange rate system and interest rates caused by the rapid developments in capital movements adversely affect the Bank's positions, and this effect is also felt in the national economy in direct proportion to the bank's balance sheet. It is an indisputable fact that the Central Bank is the decisive actor with its monetary policy decisions on credit and interest channels. The Central Bank also has an impact on the credit volume extended by commercial banks to the real sector and individuals. To the extent of changes in monetary policy, banks shape their decisions on credit policies; loan interest rates, standards applied in the loan approval process, maturity structure of loans, type of collateral and loan conditions that can be summarized in the headings are determined so that the framework of the loan supply in the form of funds borrowed by banks is determined. It is very important to identify the changes that banks implement in the lending process and to measure the effects of these changes on credit volume. When the literature on domestic and international criteria on the Bank's performance is analyzed, it is noteworthy that credit risk is at the top of the list. The performance level of the banks, which are of considerable economic importance, will directly determine the bank's presence in the system. Commercial banks constitute the largest tranche within the Turkish Banking System. In addition to the loan size, the ratios that measure credit performance have been taken into consideration and analyzed in the last three years platform by taking into consideration the NPL ratios and capital adequacy ratios